Power, social exchanges and tourism in Langkawi: Rethinking resident perceptions - Kayat, Kalsom (John Wiley & Sons, 2002)
A study was undertaken among the residents on Langkawi Island, Malaysia to explore the utility of a combination of social exchange and power theories to explain residents' attitudes toward tourism and to examine how residents' evaluation of the impact of tourism influences their attitudes. In-depth, semi-structured interviews were conducted with 46 residents.The study concludes that the combination of social exchange and power theories is more useful than social exchange theory alone in understanding residents' attitudes concerning the impact of tourism. However, residents' general values, dependence on tourism, and ability and willingness to adapt moderate the influence of power on residents' evaluation of the impact of tourism. Copyright © 2002 John Wiley & Sons, Ltd.